2015
DOI: 10.3935/rsp.v22i2.1219
|View full text |Cite
|
Sign up to set email alerts
|

Povezanost socijalne podrške i nekih aspekata roditeljstva u obiteljima s djecom s teškoćama u razvoju

Abstract: Ključne riječi: roditeljstvo, dijete s teškoćama u razvoju, socijalna podrška.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
0
10
0
4
Order By: Relevance
“…They felt a lack of professionals' interest in their child's condition (McGracey and Hart 2008;Tsai and Wang 2009;Pansini 2011;Chaij et al 2014). The results from Leutar and Oršulić's study (2015) shows that parents of children with developmental disabilities estimated that centres for social welfare and schools are not important sources of support in their lives (Leutar and Oršulić 2015). The participants in the Blaži and Kolarić study (2015) stated that professionals are not emphatic and do not provide systematic information how to achieve social rights for their children.…”
Section: Discussionmentioning
confidence: 99%
“…They felt a lack of professionals' interest in their child's condition (McGracey and Hart 2008;Tsai and Wang 2009;Pansini 2011;Chaij et al 2014). The results from Leutar and Oršulić's study (2015) shows that parents of children with developmental disabilities estimated that centres for social welfare and schools are not important sources of support in their lives (Leutar and Oršulić 2015). The participants in the Blaži and Kolarić study (2015) stated that professionals are not emphatic and do not provide systematic information how to achieve social rights for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Socijalna podrška je jedan od najvažnijih resursa koje obitelj može dobiti, a može biti formalna i neformalna (Rusu, 2019). Ona uključuje fizičku i materijalnu pomoć, promjenu stavova, dijeljenje resursa i informacija, kao i emocionalnu i psihološku pomoć (Leutar i Oršulić, 2015). Formalni oblik podrške čine profesionalna podrška stručnjaka, primjerice edukacijskog rehabilitatora, kao i državnih institucija i javne politike, dok se neformalna odnosi na podršku šire okoline, prijatelja, vjerske zajednice (Rusu, 2019) i široko dostupnih informacija poput medija, interneta i literature (Vlah i sur., 2019).…”
Section: Oblici Podrškeunclassified
“…The aim of the work involving parents of children with developmental difficulties living in the Dubrovnik-Neretva County [11] was to gain insights into social support and some aspects of parenting. The research has shown the importance of all forms of support: emotional, financial, practical and counselling assistance received within the family, and spousal support is the most important and most prominent.…”
Section: Perceived Social Support In Mental Healthmentioning
confidence: 99%